Oscillatory dynamics of motor learning across adulthood life span: a systematic review - Jahanian-Najafabadi, Amir; Davoodi, Elaheh (Frontiers in Aging Neuroscience, 2025)
Motor learning refers to a set of processes associated with practice and experience that are essential for acquiring new skills and adapting behavior throughout the lifespan. Mastery of motor skills plays a crucial role in maintaining autonomy and quality of life, particularly in aging populations. This learning process relies on internal neural mechanisms that lead to enduring changes in movement capability, yet the underlying functional and anatomical adaptations in sensorimotor circuits remain incompletely understood. These adaptations are often influenced by both task characteristics and age, highlighting the need for a deeper understanding of brain activity related to motor learning. In this pre-registered systematic review, we synthesized evidence from experimental studies and randomized controlled trials (RCTs) examining the relationship between motor learning and brain activities, specifically as measured by resting-state and task-related electroencephalography (EEG). We conducted a comprehensive literature search, identifying studies published in English between 2008 and May 2025 from PubMed, Scopus, and Web of Science databases and identified from web pages. After initial screening of 1,910 articles by title and abstract, a total of 80 studies met the eligibility criteria and were included in the final review. Studies were assessed for methodological quality in accordance with PRISMA guidelines. Our review focuses on EEG oscillatory activity across young, middle-aged, and older adults during motor skill acquisition, motor learning, adaptation and motor inhibitory control. We examined whether specific EEG features are linked to predicting motor learning performance, and explored how oscillatory patterns vary by task type, complexity, and age. By integrating findings across diverse studies, this review aims to advance our understanding of the neural mechanisms that support motor learning and its dimensions and inform the development of targeted, age-appropriate empirical research in healthy populations.Systematic review registration: CRD42024569699.